‘Hybrid Practices’ between Art, Scholarly Writing and Documentary – The Digital Future of the Essay? (Ticontre. Teoria Testo Traduzione, 2018)
This contribution explores in how far emerging interactive configurations can be regarded as isomorphisms of essayistic writing in the digital. The framework of thought is based on considerations on essayistic writing (Montaigne, Benjamin, Adorno), ‘new media’ (Manovich) as well as digital storytelling, remediation (Bolter and Grusin) and practices of `interactive factuals' (Miles). All this feeds into a transdisciplinary understanding of interactive digitext and serves as a point of departure for a discussion of database documentary as a possible `  digital future' of the essay. Questions in this context arise with regard to the transformation of conventions and techniques of `traditional essayistic writing', narrative and rhetorical principles into digital non-fiction. In how far do the specific characteristics of digital environments such as non-linearity, interactivity and plurivocality affect notions of authorship and argument? Are there unique features of digital essays that afford new forms of addressing the reader? And what forms of hybridization can be identified? To illustrate the argument, Public Secrets will be analysed. Important issues will be the concept of interface as argument, the notion of the author as ‘context-provider’ and critical reflections on the conditions of insight and knowledge in procedural, interactive media environments. Questo contributo indaga fino a che punto le emergenti configurazioni interattive possono essere considerate come isomorfismi della scrittura saggistica nell’ambito del digitale. La cornice teorica del lavoro si basa su considerazioni riguardanti la scrittura saggistica (Montaigne, Benjamin, Adorno), i “nuovi media” (Manovich), nonché lo storytelling digitale, la rimediazione (Bolter and Grusin) e la pratica dei “fatti interattivi” (Miles). Tutto ciò alimenta una comprensione transdisciplinare del digitext interattivo e funge da punto di partenza per un esame del database documentario come possibile “futuro digitale” del saggio. Ciò suscita degli interrogativi riguardo alla trasformazione delle convenzioni e delle tecniche della “tradizionale scrittura saggistica” e dei principi della narrativa e della retorica all’interno della non-fiction digitale. Fino a che punto le caratteristiche specifiche dei mezzi digitali, come l’assenza di linearità, l’interattività e la plurivocalità influenzano i concetti di autorialità e discorso? È un effetto esclusivo dei saggi digitali sviluppare nuovi modi di rivolgersi al lettore? E quali tipi di ibridazione possono essere individuati? Per mostrare e spiegare questo dibattito, si considererà Public Secrets. Un particolare rilievo sarà attribuito all’idea di interfaccia come discorso, alla nozione di autore come ‘context-provider’ e alle riflessioni critiche sulle modalità di conoscenza e approfondimento all’interno dei contesti mediatici interattivi. PAROLE CHIAVEInteractive documentary; digitext; digital media; interface; non-linearity; plurivocality; authorship; non-fiction; essay; hybridization.